Magnetic resonance imaging does not distinguish Kallmann syndrome from normosmic isolated hypogonadotropic hypogonadism - Małgorzata Kałużna; Katarzyna Katulska; Katarzyna Ziemnicka; Pola Kompf; Bartłomiej Budny; Paweł Komarnicki; Michał Rabijewski; Jerzy Moczko; Jarosław Kałużny; Marek Ruchała (Endocrine Connections)
Introduction and objectives: Isolated hypogonadotropic hypogonadism (IHH) may be associated with pituitary gland and olfactory system disorders. We aimed to correlate findings of magnetic resonance imaging (MRI) of the pituitary gland and olfactory system in IHH patients with the patients’ olfactory phenotype. Patients and methods: The present research was a single-center retrospective case–control study. MRI patterns of the pituitary gland and olfactory system were studied in 46 patients, of whom 29 (63%) were classified on the basis of olfactometry as having Kallmann syndrome (KS) (16 patients with anosmia and 13 patients with hyposmia) and 17 (37%) as having normosmic IHH (nIHH). Results were compared with age- and sex-matched healthy controls. Genetic diagnosis was conducted in all IHH patients based on next-generation sequencing. Results: Almost 70% prevalence of pituitary hypoplasia was observed in IHH subjects. Olfactory bulb (OB) abnormalities were identified in 80.4% of all patients, both the KS (82.8%) and the nIHH (76.5%) subjects. Incidence of unilaterally abnormal, hypoplastic olfactory sulcus (OS) was equally frequent in nIHH and KS. Statistically, piriform cortical thickness was significantly lower in all patient groups than in controls. Conclusions: MRI cannot exclusively differentiate between KS and nIHH, as both conditions may present with OB and OS abnormalities. A surprisingly high frequency of olfactory system abnormalities was observed in nIHH patients, while anterior pituitary hypoplasia was prevalent across all IHH patients. Notably, OB abnormalities were more predominant in KS patients than in those with nIHH.